Determinants of decision-making for the initiation of resuscitation: a mixed-methods systematic review of barriers and facilitators - Golshan Moghbeli; Fariborz Roshangar; Amin Soheili; Fazlollah Ahmadi; Hossein Feizollahzadeh; Hadi Hassankhani (International Journal of Emergency Medicine)
Abstract Aim This study aimed to comprehensively examine the factors influencing healthcare providers’ decision-making for initiation of resuscitation (IOR). Background In-hospital resuscitation survival hinges on timely and effective interventions. Despite guidelines, decision-making during resuscitation remains challenging, impacted by both clinical and non-clinical factors. Methods A mixed-methods systematic review (MMSR) was conducted, searching PubMed, Web of Science, Scopus, and Embase in May 2024. Twenty peer-reviewed studies of adult in-hospital resuscitation decision-making (≥ 18 years) were included. Data were extracted and synthesized using the Joanna Briggs Institute (JBI) convergent integrated approach. Results A database search yielded 4398 studies, of which 1216 were duplicates. After screening 3182 unique studies, 20 articles (five qualitative, 12 quantitative, three mixed methods) were included. Data synthesis identified three overarching themes: patient, provider, and system factors. These themes encompassed barriers and facilitators to IOR. Conclusion This review underscores the importance of understanding patient-related, provider-related, and system-related factors influencing IOR. By addressing these factors, healthcare organizations can improve resuscitation practices and outcomes. Future research should focus on enhancing collaboration, communication, and resource availability while considering non-medical factors in decision-making for IOR. Relevance to clinical practice Understanding the multifaceted barriers and facilitators identified in this study can enhance the effectiveness of resuscitation protocols and ultimately improve patient outcomes during critical care situations.